Cesium excited state line shapes from 6P-9S and 5D-10F broadened by helium, argon, and methane. (February 2023) - True, Timothy M.; Kuszynski, Jason E.; Rice, Christopher A.; Pitz, Greg A.; Perram, Glen P.
Highlights: Observed broadening, shift, and asymmetry rates for the Cs 6 2 P 1 / 2 → 9 2 S 1 / 2 and 5 2 D 5 / 2 → 10 2 F 5 / 2, 7 / 2 line shapes with He, Ar, and CH 4 . The observed broadening rates are the largest in the alkali-collision partner literature, with values from 100 to 700 MHz/Torr. The observed shift rates for 5 2 D 5 / 2 → 10 2 F are the largest in the alkali-collision partner literature, with absolute values from 100 to 270 MHz/Torr. The direction of the shift and asymmetry are correlated in all cases, with a blue shift for He and red shifts for Ar and CH 4 . The collisional cross section scales linearly with polarizability of the collision partner. Abstract: Pump modulated laser absorption spectroscopy was used to measure the cesium 6 2 P 1 / 2 → 9 2 S 1 / 2 and 5 2 D 5 / 2 → 10 2 F 5 / 2, 7 / 2 line shapes with helium, argon, and methane used as collision partners. The broadening rates are 99.5 ± 3.4, 116.6 ± 1.8, 188.2 ± 3.3, 133.2 ± 1.2, 294 ± 4.5, and 710 ± 18 MHz/Torr for He, Ar, and CH 4 in 6 P − 9 S and 5 D − 10 F respectively, while the shift rates are +121 ± 21, - 29.3 ± 21, - 61 ± 16, +101.4 ± 0.8, - 273.0 ± 8.0, and - 231 ± 29 MHz/Torr. For those same transitions, the asymmetry rates are +0.18 ± 0.15, - 3.1 ± 0.14, - 3.2 ± 0.1, +0.14 ± 0.04, and - 0.32 ± 0.22 mrad/Torr, with no reported value for CH 4 along 5 D − 10 F . Broadening rates scale as expected with polarizability, shift direction is to the blue/red with He/other gases, and the direction of the asymmetry correlates to the shift.